The Structures of Conceptual Transformation in the European Space - Almekinders, Mathijs (Politologija, 2020)
This book review critiques Conceptual History in the European Space by Willibald Steinmetz, Michael Freeden, and Javier Fernández-Sebastián. The publication offers the reader a unique perspective on conceptual history by providing innovative and unique approaches that demonstrate the development of the practice in a post-Koselleckian era. The review will evaluate and dissect the collective essays, as well as the effectiveness of the new dimensions of conceptual history added by the different authors that produced this volume.